PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT ASPIRASI HIDUP INDONESIA TBK PERIODE 2015 – 2024 - Alifia Nurbaiti; Rita Satria (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the partial effect of Current Ratio (CR) on Return On Equity (ROE) at PT Aspirasi Hidup Indonesia Tbk for the period 2015 – 2024, to determine the partial effect of Debt To Equity Ratio (DER) on Return On Equity (ROE) at PT Aspirasi Hidup Indonesia Tbk for the period 2015 – 2024, to determine the effect of Current Ratio and Debt To Equity Ratio simultaneously on Return On Equity (ROE) at PT Aspirasi Hidup Indonesia Tbk for the period 2015 – 2024. The research method used is descriptive quantitative. The sample used in this study is in the form of balance sheet and profit and loss reports at PT Aspirasi Hidup Indonesia Tbk, for the period 2015 - 2024. The results of the study between the Current Ratio (CR) variable have a significant effect on Return On Equity (ROE) namely t count of 2.908> t table 2.36462 with a significance value of 0.004 <0.05, then Ho is rejected and Ha is accepted. The Debt to Equity Ratio (DER) variable has a significant effect on Return On Equity (ROE) with a t count of 2.374> t table 2.36462 with a significance value of 0.002 <0.05, then H₀ is rejected and Hₐ is accepted. The Current Ratio (CR) and Debt to Equity Ratio (DER) variables simultaneously have a significant effect on Return On Equity (ROE) with a calculated F value of 6.525 with a significance value of 0.000 < 0.05.